The prediction formula of mesiodistal width of unerupted permanent canine and premolars from a group of Vietnamese, a preliminary study - Manopatanakul, Somchai; Houng, Vu Thu; Thiradilok, Sasipa (Mahidol Dental Journal, 2018)
The purpose of this study was to create new equations and to test their validity for estimating the sum of mesiodistal tooth sizes of unerupted canine and premolars of Vietnamese children. Two hundred and forty permanent teeth, including central incisors, through first molars were measured on twenty dental casts of Vietnamese. Correlation coefficient of all possible combinations of predictor were evaluated. Cross validation was also conducted both for selection of the prediction-model and validation of the prediction-result. Correlation coefficient and leave-one-out cross validation mean absolute error and root mean square error (LOOCV MAE and RMSE) were finished and indicated that the best prediction model was to use the width of mandibular central incisor and maxillary first molar (Md1Mx6) to predict the width of canine and premolars. Since there was no significant difference for sexual dimorphism (p>0.01), combined gender equations were developed from the regression analysis. The maxillary prediction formula was that Y= 0.77X+9.8 and the mandibular equation was that Y= 1.02X+5.1 where Y represented the predicted widths of canine and premolars and X represented the widths of mandibular central incisor and maxillary first molar (Md1Mx6). Validation as finished by LOOCV MAE and RMSE indicating that the error of these newly developed prediction equations was acceptable. LOOCV MAEs were 0.55 and 0.71 mm for maxillary and mandibular teeth, respectively. Further, these equations may be used with further investigation on larger sample or different specific geographic populations in Vietnam.